Drug-induced sinusoidal obstruction syndrome: a real-world pharmacovigilance study based on the FDA Adverse Event Reporting System (FEARS) - Cuicui Sun; Xiaoyan Yang; Lili Wang; Linlin Tang; Jinhua Chen (BMC Pharmacology and Toxicology)
Abstract Background Hepatic Sinusoidal Obstruction Syndrome (SOS) represents a rare but serious adverse drug reaction. This study aimed to identify the medications most frequently associated with SOS risk through the analysis of the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database. Methods We queried the FAERS database using OpenVigil 2.1 to search for all reported cases of SOS from 2004Q1 to 2022Q3. The 50 most frequently reported medications were ranked based on reported odds ratio (ROR) and proportional reporting ratio (PRR) values. We also compared these drugs with those reported in the LiverTox® database to assess consistency in hepatotoxicity reporting. Results A total of 1,976 SOS reports were indentified within the selected study period. Oxaliplatin was the most frequently reported medication associated with SOS, whereas the drug exhibited the strongest association with SOS death was busulfan. Disproportionality analysis revealed that the top five medications with the greatest association with SOS were tioguanine, inotuzumab ozogamicin, gemtuzumab ozogamicin, busulfan, and dactinomycin. Approximately half of the top 50 drugs (28 based on ROR and 27 based on PRR) were not outlined in LiverTox®. Conclusions Our study offers a potential list of drugs commonly associated with SOS and identified several novel drugs associated with SOS that had not been previously described in LiverTox®. Clinical trial number Not applicable.